Commitment of tourism and non-tourism graduates in pursuing career in tourism industry - Reyes, Lara Micaela. Santos, Louise Andrea D. Sawali, May Ann o. Silvestre, Julia Robert G. 4 0 16; 5
ABSTRACT: This study aims to examine the level of commitment of Tourism Graduates and Non-Tourism Graduates in pursuing career in Tourism Industry since not all employees in this field of Industry are Tourism Graduates. Some of them came from different courses. The purpose of this study in to know the circumstances between the performance and the level of commitment of Tourism and Non-Tourism employees in pursuing career inside the industry. A descriptive design was used for this study. This study use-self-reporting assessment tool designed to obtain the commitments of employees in the tourism industry in pursuing their career. The data analysis applied quantitative method which is explaining phenomena by collecting numerical data that are analysed using mathematical methods. The samples of the study are the employees working in the Tourism Industry in Metro Manila specifically in (NAIA) Ninoy Aquino International Airport, Makati and Malate where most numbers of Travel Agencies and Airline companies are located. The instrument has two parts. The first component is a checklist of demographic profiles of the respondents consisting of six items (gender, age, educational back ground, civil status, length of service, and rank in the organization) were found to have correlations to factors that affecting their commitments towards in pursuing their career. There were 4 problems in this study upon which answers were sought. The findings in the study revealed the level of the organizational commitment of both Tourism and Non-Tourism Graduates in pursuing career in Tourism industry can affect their performance in their career.
Undergraduate Thesis: (B.S. in Travel and Tourism Management) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2